Gender-Based Violence Patterns: A Study Applied on the Female Survivors Residing in “Dar Al Wefaq Al-Osari” - Ali Hussein, Iman Salim Ayoub“; Akroush , Lubna Judah (Dirasat: Human and Social Sciences, 2024)
Objective: This study aims to identify patterns of gender-based violence, including patterns of social, psychological, physical, economic, health, sexual, and legal violence Methods: The study adopted the qualitative approach, designing a model for semi-structured individual interviews. In-depth interviews were conducted with all the survivors who turned to the Dar Al Wefaq Al-Osari in Amman and Irbid branches between 26/07/2020 and 11/10/2020, totaling 18 survivors. The interview form included questions about survivors’ primary data, as well as questions aimed at identifying patterns of violence committed against survivors. Results: The study concluded that the survivors suffer from various forms of violence, including psychological, social, and economic. More than half of the survivors are aged between (14-23) years, and half of them have got primary education only. The study also found that psychological violence is the most common type of gender-based violence among survivors, as the number of survivors who were exposed to psychological violence reached (18). The types of this violence were insults, cursing, ridicule, and mockery followed by physical violence, as the number of those who were subjected to physical violence reached (7) survivors. The forms of this violence were bruising, contusions, fractures, and serious injuries. The last type of violence is legal violence, as (1) survivor only was exposed to legal violence. Conclusions: To address these issues, the study recommends implementing programs to raise women’s awareness of their social and legal rights, encouraging women to seek help from social support centers when confronted with violence, and providing more support programs for survivors to help them overcome the aftermath of such violence.